Integration of distributed generation in electrical grid: Optimal placement and sizing under different load conditions. (October 2019) - Essallah, Sirine; Khedher, Adel; Bouallegue, Adel
Abstract: This paper proposes a novel approach for the placement and sizing of distributed generation (DG) ensuring voltage stability and reducing total power losses in electrical grid. The main concern of the proposed method is to guarantee voltage stability along with load fluctuations, while selecting optimal DG sites and power capacities. First, vulnerable buses are determined using Voltage Stability Margin Index (VSMI). Optimum size of DG unit is computed using Matlab curve-fitting approximation. For each load level, optimal DG size and its corresponding site are recomputed. General expressions for DG power capacity are established. For different load scenarios, the determined DG locations and size are always valid. The proposed method is implemented on the 33-bus and the 69-bus distribution systems using PSAT MATLAB toolbox and results are compared to other techniques published in the literature. The obtained results prove the effectiveness, the robustness and the good performances of the proposed method.